2007
DOI: 10.1002/clc.18
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and Vasopressin Antagonism in Congestive Heart Failure

Abstract: SummaryIn a national heart failure registry, hyponatremia (serum sodium <130 mEq/L) was initially reported in 5% of patients and considered a risk factor for increased morbidity and mortality. In a chronic heart failure study, serum sodium level on admission predicted an increased length of stay for cardiovascular causes and increased mortality within 60 days of discharge. Hyponatremia in patients with congestive heart failure (CHF) is associated with a higher mortality rate. Also, by monitoring and increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…The definition of the specific cut-off value of serum sodium varies in different trials because of the different study populations. [45][46][47] Through analysis, we found the optimal threshold of the serum sodium level was 136.6 mmol/L in our cohort, which was similar to the definition in the ACTIVCHF trial. 48) Kaplan-Meier analyses demonstrated reduced survival in patients with serum sodium higher than 136.6 mmo/L.…”
Section: Discussionsupporting
confidence: 76%
“…The definition of the specific cut-off value of serum sodium varies in different trials because of the different study populations. [45][46][47] Through analysis, we found the optimal threshold of the serum sodium level was 136.6 mmol/L in our cohort, which was similar to the definition in the ACTIVCHF trial. 48) Kaplan-Meier analyses demonstrated reduced survival in patients with serum sodium higher than 136.6 mmo/L.…”
Section: Discussionsupporting
confidence: 76%
“…RAAS is also known to be inappropriately elevated among heart failure patients. 13) RAAS activation triggers hypokalemia in the tubules of the kidney, which is one of the causes of the secondary renal diabetes insipidus. It was reported that hypokalemia caused a reduction in the intracellular level of cAMP (cyclic adenosine monophosphate), which acts as the secondary messenger of AVP, and downregulated aquaporin-2 in the collecting duct.…”
Section: Article P461mentioning
confidence: 99%
“…Physiologically, hyperosmolality increases, whereas hypoosmolality decreases plasma AVP concentration (4). However, in diverse pathological syndromes, such as hepatic cirrhosis (35), congestive heart failure (37,38), and nephrogenic syndrome (23,26,48), a decrease in osmolality fails to inhibit AVP release. This AVP release leads to water retention and contributes to the morbidity and mortality associated with these diseases (1, 22, 24, 37, 38).…”
Section: R952 Ang II Induces Trpv4 Trafficking In 4b Cellsmentioning
confidence: 99%